DESIGN OF DETECTING ACOUSTIC WAVES AT THE EXERCISE SMART MINE USING ACOUSTIC SENSOR - I Nengah Putra A; Nuri Nur Cahyono; Gesit Pratiknyo; M Sigit Purwanto (JOURNAL ASRO, 2020)
The Indonesian Navy is a unit of defense of the Republic of Indonesia (NKRI). Sea mines are explosive devices placed in waters to destroy ships. Acoustics is a branch of physics that deals with all mechanical waves in liquids, gases and solids, such as vibration, sound and ultrasonic. Arduino has made microcontroller technology more accessible and easier for even novice users. Because of this, there are special functions in audio or acoustic processing techniques aimed at using Arduino. The application of acoustic signals in the military field of the Navy, in the identification of vessels caught by the microphone receiver. The movement of objects that are caught by the microphone will be analyzed to conclude the object. From the results of the sound characteristics raised by the object, it will give a different picture for different variations of the object. Processing acoustic signals using DSP will make it easier to infer the captured acoustic signal. The circuit board used is a microphone signal amplifier and signal conditioner, for processing the audio signal obtained from the microphone and to produce output data which is the result of the process using Arduino. Analog-to-digital converter (ADC) of the microcontroller works in the voltage range from 0.0 V to +3.3 V or +5.0 V. Toachieve good sampling results, that the signal peak is close to the maximum value of the ADC. Additionally, voltage amplitudes above this threshold can damage the controller input port or produce unwanted harmonics. Therefore, a signal pre-amp circuit is needed to guarantee the appropriate audio sample signal as well as to protect the system. The test results obtained from the system analyzer frequency and signal meters can be used to identify acoustic signals. Keyword: Singnal Acoustic/michophone, controller, Arduino Uno, pre-amp frequency analyzer